Fa’āliyatu Muntadā al Mutakallimīna li Tarqiyati Mahārati al Kalāmi Ladā al Talāmīzi al Sākinīna fī Mabnā Dalwā al Rābi’i bi Ma’hadi Dāri al Lughati wa al Da’wati - Baharun, Segaf; Hanafi, Hanafi (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
Muntada al-Mutakallimin, a mandatory activity for students in these four schools, is the Darullughah Waddakwah Islamic Boarding School. The institute prepares language programs to help them improve their Arabic. At Pondok Pesantren Darullughah Wadda'wah learn four language skills with good media, strategies, programs and environment. To develop the efficiency of students' speaking skills in it, students also practice speaking in Arabic when they talk and debate with their friends and teachers in the forum. Therefore, they progress in Arabic and are better than before, especially in their speaking skills. The formulation of the problem in this study 1) How is Muntada al-Mutakkalimin to improve students' speaking skills at Darullughah Wadda'wah Islamic Boarding School 4? 2) How is the effectiveness of Muntada al-Mutakallimin in improving speaking skills for students of Darullughah Wadda'wah Islamic Boarding School 4?. Researchers used a quantitative approach. The results of this study, firstly, that to develop the efficiency of students' speaking skills, a language program, namely Muntada al-Mutakallimin, was held, including the practice of students speaking Arabic when they called and debated with their friends and teachers. in the forum Students speak Arabic. Second, the result of the first pre test and achievement test (1) on the comparison value is 6.24%. What is meant by the development of the results of the first achievement test from the results of the pretest. The comparison score between the first achievement test and the second achievement test is 86%. The meaning is the development of the results of the second achievement test from the first achievement test for the Darullughah Wadda'wah Islamic Boarding School students. In other words, the Muntada al-Mutakallimin program affected the development of their speaking skills. These results are the results of observations and interviews with supervisors and students, as well as questionnaire data. Darullughah Wadda;wah Islamic Boarding School students agree that Muntada al-Mutakallimin influenced their speech development